1988
DOI: 10.1111/j.1476-5381.1988.tb11706.x
|View full text |Cite
|
Sign up to set email alerts
|

Flunarizine inhibits endothelium‐dependent hypoxic facilitation in canine coronary arteries through an action on vascular smooth muscle

Abstract: 1 Hypoxia augments contractile responses to several vasoactive agents in canine isolated coronary arteries with intact endothelium. Calcium antagonists inhibit the further increases in tension caused by hypoxia. The present experiments were designed to determine whether the calcium-antagonist flunarizine would inhibit hypoxic contractions in isolated blood vessels through an action on the endothelium or on the vascular smooth muscle. 2 Rings of canine coronary arteries, with or without endothelium, were suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…However, the present experiment demonstrates that in the porcine coronary artery the endothelium-dependent part of the response to hypoxia is inhibited by agents that target the NO pathway, in particular inhibitors of eNOS and soluble guanylyl cyclase. The present findings thus corroborate the interpretation reached in canine arteries that NO is required in order for the endotheliumdependent hypoxic contraction to occur (22) and thus that endothelium-derived NO is likely to be the only diffusible substance (28,45) solely responsible for the phenomenon. This conclusion is strengthened by the present findings demonstrating that exogenous NO donors (DETA NONOate or sodium nitroprusside) restore the contractile response to hypoxia in preparations with endothelium treated with L-NAME.…”
Section: Discussionsupporting
confidence: 90%
“…However, the present experiment demonstrates that in the porcine coronary artery the endothelium-dependent part of the response to hypoxia is inhibited by agents that target the NO pathway, in particular inhibitors of eNOS and soluble guanylyl cyclase. The present findings thus corroborate the interpretation reached in canine arteries that NO is required in order for the endotheliumdependent hypoxic contraction to occur (22) and thus that endothelium-derived NO is likely to be the only diffusible substance (28,45) solely responsible for the phenomenon. This conclusion is strengthened by the present findings demonstrating that exogenous NO donors (DETA NONOate or sodium nitroprusside) restore the contractile response to hypoxia in preparations with endothelium treated with L-NAME.…”
Section: Discussionsupporting
confidence: 90%
“…52 In a number of isolated arteries and veins, endothelium-dependent contractions can be evoked by anoxia 14 -53 -55 ; the contractions can be inhibited by Ca 2+ -antagonists, presumably because of their action on vascular smooth muscle rather than on the endothelial cells. 55 Although the mediator of the endotheliumdependent hypoxic contraction is unknown, the possibility exists that the hypoxic endothelial cells may release a vasoconstrictor peptide like endothelin ( Figure M)."-^." EDRF and NO inhibit the adhesion and the aggregation of platelets; their antiplatelet activity is considerably augmented in the presence of prostacyclin and vice versa.…”
Section: Does the Endothelium Release Contracting Factors?mentioning
confidence: 99%
“…Besides playing an essential role in vasodilator responses by releasing endothelium‐derived relaxing factor(s) (EDRF(s)) (Furchgott & Zawadzki, 1980), the endothelial cells of certain arteries and veins can also initiate contractions of the vascular smooth muscle that surrounds them (De Mey & Vanhoutte, 1982, 1983). Bioassay studies demonstrated that the transfer of diffusible factors is involved in such endothelium‐dependent contractions (Rubanyi & Vanhoutte, 1985; Iqbal & Vanhoutte, 1988; Yang et al 2003). Theoretically, endothelium‐dependent contractions could be explained by either the withdrawal of endothelial inhibitory signals (prostacyclin, nitric oxide (NO), endothelium‐derived hyperpolarizing factor (EDHF) or the production of vasoconstrictor substances.…”
mentioning
confidence: 99%